Aerodynamic characteristics of a swept wing with spanwise blowing. - Ayers, R. F.; Wilde, M. R. (Cranfield University, 1956)
This report is the first of a series of studies to investigate the effectiveness of a spanwise blowing on the aerodynamic characteristics of low aspect ratio wings and bodies. The model used in this investigation was an untapered half-wing aspect ratio 1.39,50 degree sweep back, and mounted on a reflective plate.
An experimental investigation of the aerodynamic characteristics of a low aspect ratio swept wing with blowing in a spanwise direction from the tips.
The work described in this report was conducted as a partial requirement for the Diploma of the College of Aeronautics